Poverty, Health, and Nutrition Division (PHND) - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
Poverty, food insecurity, and poor nutrition and health are among the most pernicious problems eroding people’s quality of life and limiting their economic productivity. These are the problems that IFPRI’s Poverty, Health, and Nutrition Division (PHND) aims to understand and overcome. PHND research provides evidence on strategies to increase the incomes of poor people in developing countries, improve their livelihoods, and promote their ability to acquire skills and knowledge, access healthy diets, and live healthy and well-nourished lives. To accomplish this, the division’s researchers examine the causes of poverty, food insecurity, and malnutrition and identify effective policies and programs for addressing them, including programs in agriculture, health, education, and social protection. Issues of gender are central to this research, and several projects identify innovative ways of empowering women to maximize the impacts of such programs. PHND’s work contributes to IFPRI’s 2018–2020 Strategy, particularly in the strategic research area on promoting healthy diets and nutrition for all and the cross-cutting theme on gender. The division’s activities focus on Africa and South Asia, with a continuing presence in Latin America.